Anthraquinones from the roots of Paederia scandens - Quang, Đặng Ngọc (Vietnam Journal of Chemistry, 2014)
Chemical investigation on the ethyl acetate extract of the roots of Vietnamese Paederia scandens resulted in the isolation of one new anthraquinone, 1,3-Dihydroxy-2,4-dimethoxy-9,10-anthraquinone (1), together with three known anthraquinones, 2-Hydroxy-1,4-dimethoxy-9,10-anthraquinone (2), 1-Methoxy-2-methoxymethyl-3-hydroxy-9,10-anthraquinone (3), 1-Hydroxy-2-hydroxymethyl-9,10-anthraquinone (4). Their structures were elucidated by the combination of 2D NMR, IR, UV and high resolution EI-MS spectroscopy. These anthraquinones (1 - 4) showed strong antimicrobial activity.